The square as an outdoor market space: Exploring the potentials of Dataran Merdeka - Zakariya, Khalilah; Harun, Nor Zalina (Association of Malaysian Environment-Behaviour Researchers (AMER), 2018)
This exploratory paper presents the potentials of appropriating a temporary weekend market adjacent to a historic square as an informal activity to encourage people to engage more with Dataran Merdeka as their historic place. From employing methods of observations, mapping and interviews, the findings from this paper reveal how locating temporary market activity at Dataran Merdeka might activate this historic square as a lively social space while tapping into the existing event culture. This study suggests that the juxtaposition between the historic and the everyday can ascribe new meaning to the layers of the city’s heritage to support cultural sustainability.